Analisis Persepsi Konsumen Terhadap Kualitas Produk Lavanda Brownies Karawang - Rahmi Yuliandhari; Netti Nurlenawati; Dexi Triadinda (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study is to investigate customer experiences with Lavanda Karawang goods and examine how customers view the quality of Lavanda Brownies products. The purpose of the qualitative descriptive approach is to gain a deeper understanding of customers' experiences and views regarding the quality of Lavanda Brownies products following a purchase. Data is gathered by observation, documentation, and interviews. Primary data for this study came from informants, and secondary data came from a variety of publications. Validation tests were conducted utilizing a source triangulation method to guarantee the accuracy of the data. The findings indicated that, as one of the elements contributing to a company's competitive advantage, the impression of product quality is significant. Also, customers frequently repurchase Lavanda items.